Sub-Lethal Effect of Waterborne Cadmium Exposure on Glutathione S-Transferase and Total Protein Contents in Liver of Carnivorous Fish, Wallago attu: Concentration specific response of GST in fish - Batool, Yasmeen; Abdullah, Sajid; Naz, Huma; Abbas, Khalid (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
This research work was performed to evaluate the glutathione S-transferase activity and total protein contents in liver of carnivorous fish, Wallago attu exposed to sub-lethal concentrations (1/3rd, 1/4th and 1/5th) of cadmium for14days. Fish was sampled after 7 days interval. Spectrophotometric method was used to analyze the GST activity and protein contents. Results showed that the exposure of waterborne cadmium significantly (p<0.05) increased the GST activity in liver of fish in relation to control. However, protein contents were significantly (p<0.05) decreased due to metal exposure. It was also concluded that concentration and duration of exposure greatly influenced GST activity and total protein contents in fish. Regression analyses showed that GST activity had significantly positive relation with cadmium concentrations while protein showed significantly negative relationship with concentration.